TRAINING METHODOLOGY AND DIDACTIC BASES OF TECHNICAL MOVEMENTS OF 12-14-YEAR-OLD VOLLEYBALL PLAYERS (World Bulletin of Social Sciences, 2023)
Volleyball is a highly popular team sport that requires a range of physical and technical skills. To become a successful volleyball player, it is crucial to undergo extensive training, especially during the formative years. This article presents a comprehensive analysis of the training methodology and didactic bases of technical movements for 12-14-year-old volleyball players. It discusses the importance of mastering technical movements such as serving, passing, setting, spiking, and blocking, and how these movements vary depending on the player's position on the court. The article emphasizes the role of proper training in enhancing the technical skills of volleyball players and contributing to their overall success on the court. It provides an overview of various training methods, including repetition, drills, and game simulations, and how they can be used to develop technical movements. Furthermore, the article examines the didactic bases for training technical movements, including the principles of skill acquisition and motor learning, and how coaches can design training programs that are tailored to the specific needs of 12-14-yearold volleyball players. The article presents several case studies of successful training methodologies and provides suggestions for future research in the field of volleyball training methodology. Overall, this article serves as a valuable resource for coaches, trainers, and researchers interested in enhancing the technical skills of 12-14-year-old volleyball players